Analisis podcast sebagai media pembelajaran bahasa inggris untuk meningkatkan kemampuan speaking dan listening - anggraini, nur fika (Maliki Interdisciplinary Journal, 2025)
Podcasts are growing in popularity as a tool to help students learn English. Studies show that incorporating podcasts improves students' speaking skills from 30% to 83%. Despite some problems, such as a lack of guidance, the survey found that this activity was viewed positively by 61.1% of students and they felt more confident to speak after participating in the podcast program. The study involved 18 students who filled out a questionnaire; the majority of them agree that podcasts help them speak in English, despite some issues. In addition, podcasts are used in teaching listening in two cycles. This shows increased student participation and understanding, as well as an increase in their confidence in answering content-related questions. The results show that podcasts are an effective tool for improving listening and speaking skills.